A study of clinical outcome and patient quality of life in timing of free flap cover in type IIIB open fractures - Manakchand, Kamal Kumar; Narayan, Naveen; Chethan, Shivannaiah (International Surgery Journal, 2019)
Background: Open fractures of leg classified under type IIIB, those requiring free flap cover could be done as emergency procedure. The ideal timing has still remained controversial. Although it appears imperative to operate early and reduce length of hospital stay, costs, disability adjusted life years and put the patient back on his feet, our study was necessitated in the context of differing views regarding ideal timing of free flap. Methods: The prospective observational study was conducted for duration of 4 years between October 2015 to September 2019. Patients were taken up for free flap cover after optimization for the major surgery. Details of flap complications and the procedures for salvage were noted. At the end of one year following the injury, patient quality of life (PQOL) was tabulated for all patients. Results: Most common mode of injury was road traffic accidents. Early flaps were done in 28 and primary flaps in 22 patients. One patient had partial flap necrosis while 7 others had sub flap collections and partial flap necrosis. Duration of hospitalization was significantly lower in early flap cover group. PQOL measured with EQ-5D (EuroQol 5D) was significantly higher in the early flap covers. Conclusions: From our study we concluded that timing of free flap cover positively influenced clinical outcome of reduced hospitalization, although there was no relation of timing of free flap to flap or bone complications. The functional outcome measured by PQOL was significantly higher in patients who had microvascular reconstruction early.